The last ships from Hamburg : business, rivalry, and the race to save Russia's Jews on the eve of World War I - Ujifusa, Steven (Harper, an imprint of HarperCollins Publishers, 2023)
"The story of the mass exodus of Jews out of Eastern Europe at the turn of the 20th century and the titans of industry who made it possible"--